Predictive Value of Blood and Echocardiographic Indicators for Nonvalvular Atrial Fibrillation in Postmenopausal Women - Lei Song; Xiao‐Ping Shen; Jian‐Rong Cai; Hong‐Lei Zhang; Gui‐Ru Li; Jing Shi (Annals of Noninvasive Electrocardiology)
ABSTRACT Objective To evaluate the association and predictive value of midregional pro‐atrial natriuretic peptide (MR‐proANP), bone morphogenetic protein (BMP‐7), and left atrial diameter (LAD) with nonvalvular atrial fibrillation (NVAF) in postmenopausal women. Methods This retrospective study included 288 postmenopausal women treated at Chongming Hospital Affiliated to Shanghai University of Medicine and Health Sciences from January 2022 to October 2024. Patients were categorized into the NVAF and control groups based on electrocardiogram findings. Observation indicators were LAD, MR‐proANP, BMP‐7, homocysteine (Hcy), and free thyroxine (FT4). Echocardiography excluded valvular disease and measured LAD. Serum biomarkers were quantified using ELISA. Logistic regression identified independent risk factors, and ROC curves assessed predictive value. Results Of the 288 participants, 175 (61%) had NVAF. MR‐proANP (425.8 vs. 289.4 nmol/L, p < 0.001), and LAD (38.4 vs. 32.5 mm, p < 0.001) were significantly higher in the NVAF group, whereas BMP‐7 levels were lower (2.22 vs. 2.67 pg/L, p < 0.001). Additionally, Hcy (13.59 vs. 11.64 nmol/L, p = 0.023) and FT4 (16.91 vs. 15.85 nmol/L, p = 0.014) levels were also significantly elevated in the NVAF group. Multivariate logistic regression showed MR‐proANP (OR 1.005, 95% CI 1.001–1.008), BMP‐7 (OR 0.338, 95% CI 0.226–0.504), and LAD (OR 1.291, 95% CI 1.205–1.383) as independent risk factors for NVAF. Combined ROC analysis for MR‐proANP, BMP‐7, and LAD demonstrated an area under the curve (AUC) of 0.803, indicating superior predictive sensitivity and specificity than one indicator alone. Conclusion MR‐proANP, BMP‐7, and LAD are independent risk factors for NVAF in postmenopausal women. Their combined measurement provides valuable predictive insights, aiding in clinical decision‐making.